Optimalisasi Komunikasi Penyuluhan Pertanian Dalam Sekolah Lapang Iklim Stasiun Klimatologi Kupang - Donna Isra SIlaban; Yosep Riang; Mikhael Rajamuda Bataona; Viona Menda; Angelina Bajo (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Climate change has an impact on decreasing agricultural production due to changes in cropping patterns. Farmers have difficulty determining planting times to adapt to climate conditions due to a lack of understanding of climate information. Therefore, agricultural education regarding climate information is conveyed by the government to the public through the Meteorology, Climatology and Geophysics Agency (BMKG). The climate information is then conveyed by BMKG through the climatology station in the Climate Field School (SLI) program. The aim of this research is to determine the optimization of agricultural extension communication in the Kupang climatology station's climate field school. The stages of this research method start from a literature review, data collection in the form of primary data and secondary data, then the data is analyzed. The research results show that optimizing agricultural extension communication in the Kupang Climatology Station SLI is carried out by integrating local wisdom with science. The use of local languages by extension agents is an appropriate extension communication strategy used by SLI. This collaboration creates an understanding of how to read climate change which is used to determine the right planting time.